Pentingnya Pendidikan Sains Bagi Perkembangan Kognitif Dan Kreatifitas Anak Usia Dini - Churiyah Churiyah; Ruqoyyah Fitri (Harmoni Pendidikan : Jurnal Ilmu Pendidikan, 2024)
Science education in early childhood plays a crucial role in their cognitive and creative development. Science education in early childhood also has a vital role in supporting cognitive and creative development. This research aims to explore the benefits provided by science education in stimulating critical thinking, problem solving and innovation skills in children. Through qualitative and quantitative approaches, data is collected from various sources, including classroom observations, interviews with educators, and analysis of children's learning outcomes. The results showed that children who were involved in science activities from an early age showed significant improvements in cognitive skills such as memory, concentration and analytical abilities. Apart from that, science education has also been proven to encourage children's creativity by enriching their imagination and ability to think outside the box. This article concludes that the integration of science education in the PAUD curriculum not only supports children's intellectual development but also forms a strong foundation for creativity and innovation in the future. Therefore, it is important for educators and policy makers to recognize and prioritize science education as an essential component in early childhood education, science education must be a top priority in early childhood education strategies by educators and policy makers.